Aliphatic isocyanurates and polyisocyanurate networks - Driest, P. J. (2017)
The production, processing, and application of aliphatic isocyanate (NCO)-based thermosets such as polyurethane coatings and adhesives are generally limited by the surprisingly high viscosity of tri-functionality and higher-functionality isocyanurates. These compounds are essential crosslinking additives for network formation. However, the mechanism by which these high viscosities are caused is not yet understood. In this work, model aliphatic isocyanurates were synthesized and isolated in high purity (>99%), and their viscosities were accurately determined. It was shown that the presence of the NCO group has a strong influence on the viscosity of the system. From density functional theory calculations, a novel and significant bimolecular binding potential of À8.7 kJ/mol was identified be- tween NCO groups and isocyanurate rings, confirming the important role of the NCO group. This NCO-to-ring inter- action was proposed to be the root cause for the high viscosities observed for NCO-functional isocyanurate systems. Molecular dynamics simulations carried out to further confirm this influence also suggest that the NCO-to- ring interaction causes a significant additional contribution to viscosity. Finally, model functional isocyanurates were further reacted into densely crosslinked polyisocyanurate networks which showed interesting material properties.